Accounting information system security a survey of e-commerce companies in Malaysia - Raja Mohd Ali, Raja Haslinda; Mat Saat, Rafeah; Mohd Lazim, Marlina (Universiti Utara Malaysia, 2004)
The reliance on information and rapidly changing technology in Malaysia has forced organizations especially in e-commerce industry to implement comprehensive information security programs and procedures to protect their information assets. Failure to secure information or to make it available when required to those who need it can and does, lead to financial loss. Thus, this study concentrates on security threats towards computerized accounting system in e-commerce industry in Malaysia. It also investigates the controls that have been implemented in this industry to prevent and detect security breaches. A survey approach is adopted to gather the required data. Results of study show that the main potential threats faced by e-commerce companies are accidental destruction of data, accidental entry of bad data, sharing passwords and unauthorized distribution of data. These e-commerce companies also show that they did routine security audits and to take action when confronted with computer intrusion and destruction.